Ecological preference of the diving bell spider Argyroneta aquatica in a resurgence of the Po plain (Northern Italy) (Araneae: Cybaeidae) - Mammola, Stefano; Cavalcante, Riccardo; Isaia, Marco (Fragmenta entomologica, 2016)
The diving bell spider Argyroneta aquatica is the only known spider to conduct a wholly aquatic life. For this reason, it has been the object of an array of studies concerning different aspects of its peculiar biology such as reproductive behavior and sexual dimorphism, physiology, genetic and silk. On the other hand, besides some empirical observations, the autoecology of this spider is widely understudied. We conducted an ecological study in a resurgence located in the Po Plain (Northern Italy, Province of Vercelli) hosting a relatively rich population of Argyroneta aquatica, aiming at identifying the ecological factors driving its presence at the micro-habitat level. By means of a specific sampling methodology, we acquired distributional data of the spiders in the study area and monitored physical-chemical and habitat structure parameters at each plot. We analyzed the data through Bernoulli Generalized Linear Models (GLM). Results pointed out a significant positive effect of the presence of aquatic vegetation in the plot. In addition, the presence of A. aquatica was significantly associated with areas of the resurgence characterized at the same time by high prey availability and low density of predators. Considering the ecological importance and rarity of this species, we update and revise the data on the distribution of A. aquatica in Italy.